Penerapan Asas Prior In Tempore dan Torrens System dalam Putusan Mahkamah Agung terkait Sertipikat Ganda: The Application of the Prior In Tempore Principle and the Torrens System in Supreme Court Decisions Regarding Duplicate Certificates - Muntaz, Nabila Aleysafa; permadi, Iwan; Herlindah (Faculty of Law, Universitas Brawijaya, 2026)
This research examines the application of the Prior in Tempore and Torrens System principles in resolving double land certificate disputes within Indonesia's land registration framework, as reflected in Supreme Court Decision No. 309 PK/PDT/2021. The study is motivated by the recurring legal uncertainty arising from conflicting certificates on a single plot of land, which creates a dilemma between upholding historical ownership justice and enforcing formal legal certainty based on registered titles. The objectives are to analyze the conflict and adaptation between these two principles in Indonesia's system and to examine the judicial reasoning (ratio decidendi) employed in the aforementioned Supreme Court ruling. Employing a normative juridical method with statutory, conceptual, case, and comparative approaches, the study finds that while Indonesia’s hybrid system attempts to integrate elements of both principles, the Supreme Court's decision prioritized the Prior in Tempore doctrine. The Court ruled in favor of the holder of the earlier-issued certificate, effectively sidelining the good faith protection stipulated in Article 32(2) of Government Regulation No. 24 of 1997, which is a key feature of the adapted Torrens System. The ruling underscores the system's failure to provide absolute legal certainty and highlights the absence of a state guarantee fund to compensate parties harmed by administrative errors in land registration.